The Influence of Self-Leadership and Proactive Personality Towards Innovative Work Behavior of Employees - Kastyaningrum, Tiara Putri; Ramli, Abdul Haeba (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study examines the influence of self-leadership and proactive personality on innovative work behavior, with resilience as a moderator, in the manufacturing sector of Tangerang Regency, Indonesia. Against the backdrop of global competition demanding adaptive and innovative human resources, a quantitative approach using Structural Equation Modeling was applied to data from manufacturing employees. Validated instruments confirmed that self-leadership and proactive personality significantly drive innovative behavior, while resilience not only directly enhances innovation but also strengthens the self-leadesrhip – innovation relationship. Finding underscore the synergistic interplay of these three factors in foresting an innovation work environment. Partical implications include intergrated resilience training programs, proactive personality – based recruitment strategies, and innovation reward system. The theoretical contribution lies in integrating proactive personality as a novel variable and demonstrating resilience’s dual role (direct and moderating) in an Indonesian manufacturing context, providing a sustainable human resource development framework for industrial competitiveness.